Can preterm birth affect the palate morphology? A systematic review (Research, Society and Development, 2021)
The purpose of this review was to evaluate whether preterm birth affects palate morphology. Opened electronic search in PubMed (MEDLINE), Lilacs, Scopus and Web of Science was conducted and a partial search of the gray literature using Google Scholar, Open Gray and ProQuest. We included studies with infants born prematurely (born up to the 37th week of gestation and weighing less than 2.500 g) and not preterm infants; intubated and not intubated. Two independent reviewers performed study selection, data extraction, and bias risk assessment. Selection criteria included observational, retrospective and prospective, randomized or nonrandomized cohort studies and control studies. There was no restriction on publication time and article language. A total of   2344 articles were found after the duplicates were removed, of which 7 met the inclusion criteria and were submitted to a Bias Risk analysis using MASTARI. Scientific evidence was found for altered palate morphology among premature infants, and oral intubation was a contributing factor for such alterations. Based on this review, it is concluded that premature birth changes palate morphology, when prematurity is associated with the use of the orotracheal tube.